2020
DOI: 10.1002/ccd.28797
|View full text |Cite
|
Sign up to set email alerts
|

Multiple unplanned readmissions after discharge for an admission with percutaneous coronary intervention

Abstract: Objective This study aims to describe temporal trends, characteristics, and clinical outcomes of patients with more than one unplanned readmission within 30 and 180 days after admission with percutaneous coronary intervention (PCI). Background There is limited understanding of multiple readmissions after PCI. Methods Patients undergoing PCI between 2010 and 2014 in the U.S. Nationwide Readmission Database were evaluated for unplanned readmissions at 30 and 180 days after discharge. Trends in multiple readmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(18 reference statements)
0
4
1
Order By: Relevance
“…In this study, the readmission rate of patients was about 25%, higher than the results of many domestic and foreign studies [37][38][39]. Readmissions due to hypertension accounted for 48.15% of total readmissions.…”
Section: Plos Onecontrasting
confidence: 57%
“…In this study, the readmission rate of patients was about 25%, higher than the results of many domestic and foreign studies [37][38][39]. Readmissions due to hypertension accounted for 48.15% of total readmissions.…”
Section: Plos Onecontrasting
confidence: 57%
“…Recent studies, however, have suggested a lack of clarity regarding this hypothesis. Given that PCI is an increasingly common procedure in the United States (US) with high rates of readmission, this ambiguity is concerning [ 5 , 6 ]. Compelling evidence has even revealed a lack of complete understanding surrounding the biochemical mechanisms of cardiac troponin release, which further challenges these previous notions [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It showed nearly 20% of patients were readmitted for cardiovascular events within 1 year of PCI in the previous study ( 20 ). Thus unplanned readmission in the early post-procedure period after PCI is considered to be a costly and common adverse outcome ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%